Odpowiedź :
Odpowiedź:
a) (2 - 1 4/9) * (2 3/5 - 1 3/5 : 4)= (2/1 - 1 4/9) * (2 3/5 - 1 3/5 : 4)= (2/1 - 13/9) * (2 3/5 - 1 3/5 : 4)= (18/9 - 13/9)* (2 3/5 - 1 3/5 : 4)= 5/9 * (2 3/5 - 1 3/5 : 4)= 5/9 * (2 3/5 - 8/5 : 4/1)= 5/9 * (2 3/5 - 8/5 * 1/4)= 5/9 * (2 3/5 - 32/20 * 5/20)= 5/9 * (2 3/5 - 17/20)= 5/9 * (13/5 - 17/20)= 5/9 * (52/20 - 17/20)= 5/9 * 35/20= 35/36
b) 0,7+ 0,3 * (2 * 1,8 + 6,4)= 0,7+ 0,3 * (3,6 + 6,4)= 0,7+ 0,3 * 10= 0,7+ 3= 3,7
c) (2 * 1/4 + 3* 0,4 + 1,6) * 2/5= (2 * 0,75 + 3 * 0,4 + 1,6) * 2/5= (1,5 + 1,2 + 1,6) * 2/5= 4,7 * 0,4= 1,88
Szczegółowe wyjaśnienie:
Mam nadzieję, że pomogłam
Odpowiedź:
A) (2 - 1 4/9) * (2 3/5 - 1 3/5 : 4) = 5/9 * (2 3/5 - 8/5 * 1/4)= 5/9 * (2 3/5 - 2/5) = 5/9 * 2 1/5 = 5/9 * 11/5 = 11/9 = 1 2/9
B) 0,7 + 0,3 * (2 * 1,8 + 6,4) = 0,7 + 0,3 * (3,6 + 6,4) = 0,7 + 0,3 * 10 = 0,7 + 3 = 3,7
C) (2 * 1/4 + 3 * 0,4 + 1,6) * 2/5 = (1/2 + 1,2 + 1,6) * 2/5 =(0,5 + 1,2 + 1,6) * 2/5 3,3 * 2/5 = 33/10 * 2/5 = 33/25 = 1 8/25
proszę bardzo